2010
DOI: 10.1016/j.jesp.2009.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Threatened selves and differential prejudice expression by White and Black perceivers

Abstract: Previous theorizing suggests that often-stigmatized individuals may be just as likely, if not more likely, than infrequently stigmatized individuals to protect self-regard by derogating members of low-status groups after receiving negative feedback from high-status others. Often-stigmatized individuals, however, can discount criticism from these high-status others as reflecting prejudice,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Feelings about one’s self is linked to racial attitudes; ego threats increase negative racial attitudes, but affirming the self increases positive racial attitudes. Threats to the self can lead people to judge an ethnic minority job applicant more harshly, but affirming the self diminished discrimination (Fein & Spencer, 1997; Shapiro, Mistler, & Neuberg, 2010). Self-affirmed White participants report perceiving more racism in discriminatory actions (Adams, Tormala, & O’Brien, 2006) and more acceptance that White privilege exists in society (Knowles & Lowery, 2012; Knowles, Lowery, Chow, & Unzueta, 2014; Phillips & Lowery, 2015).…”
Section: Experiencing Vicarious Suppression: Two Hypothesesmentioning
confidence: 99%
“…Feelings about one’s self is linked to racial attitudes; ego threats increase negative racial attitudes, but affirming the self increases positive racial attitudes. Threats to the self can lead people to judge an ethnic minority job applicant more harshly, but affirming the self diminished discrimination (Fein & Spencer, 1997; Shapiro, Mistler, & Neuberg, 2010). Self-affirmed White participants report perceiving more racism in discriminatory actions (Adams, Tormala, & O’Brien, 2006) and more acceptance that White privilege exists in society (Knowles & Lowery, 2012; Knowles, Lowery, Chow, & Unzueta, 2014; Phillips & Lowery, 2015).…”
Section: Experiencing Vicarious Suppression: Two Hypothesesmentioning
confidence: 99%
“…Research reveals that, compared to members of high‐status groups, members of low‐status groups are more likely to identify with their ingroup and discriminate against or hold less favorable attitudes toward outgroups (Bettencourt et al, ). For example, Shapiro, Mistler, and Neuberg () found that Black participants were significantly more likely to derogate and express prejudice toward high‐status infrequently stigmatized Whites than they were to low‐status, stigmatized groups.…”
Section: Ingroup Comparison and The Self‐conceptmentioning
confidence: 99%
“…We now know much about dominant group members' experiences, but research conducted on, and from the perspective of, dominant majority group members does not always generalize to members of lower-status, disadvantaged minority groups (e.g., Craig & Richeson, 2016;Dovidio, Gaertner, & Saguy, 2007;Shapiro et al, 2010;Shapiro & Neuberg, 2008). It is essential for social psychological research to incorporate research participants and frameworks that better reflect the broad diversity of human social behavior, attitudes, and cognition.…”
mentioning
confidence: 99%
“…This is in part because very little empirical research examines members of stigmatized groups as anything other than passive victims of discrimination (Shelton, 2000, 2003). Indeed, the limited research that has explored disadvantaged group members as active agents in intergroup relations reveals that the processes and outcomes that are typically found within majority group members do not always generalize to members of frequently stigmatized groups (e.g., Craig & Richeson, 2012; Shapiro, Mistler, & Neuberg, 2010; Shapiro & Neuberg, 2008). As a result, researchers continue to call for empirical work to fill this gap in the intergroup relations literature—to treat members of disadvantaged groups as active participants in intergroup relations (Craig & Richeson, 2016; Major & Vick, 2005; Richeson & Craig, 2011; Shelton, 2000).…”
mentioning
confidence: 99%